Kink Effect in AlGaN/GaN HEMTs Induced by Drain and Gate Pumping - Wang, Maojun; Chen, Kevin J. (IEEE ELECTRON DEVICE LETTERS, 2011)
Kink effects are studied in conventional AlGaN/GaN high-electron-mobility transistors by measuring their current-voltage characteristics with various bias sweeping conditions at drain and gate terminals. It is found that the kink effect is induced by drain and gate pumping. The magnitude of kink is directly related to the maximum drain voltage and current levels during on-state operation. The hot electrons in the 2-D electron gas channel generated under high drain bias could be injected into the adjacent epitaxial buffer layer where they can be captured by donor-like traps. Hot electron trapping and the subsequent field-assisted de-trapping is suggested to be the dominant mechanism of kink generation in the studied device. The extracted activation energy of the traps accounting for the kink effect is 589 +/- 67 meV from temperature-dependent transient measurement, and is close to the energy of the E-2 trap widely reported in GaN layers.